Implications of the Date formulas of the kings of the Dynasty of Ur III (2112-2004 B.C) - Taqwa Bashar Abd Alhaq Mohhamed Ali, Assistant archaeologist Researcher; Hassanein Haydar Abdulwahed, Prof. Dr. (lark, 2026)
The Date formulas of the kings of the Dynasty of Ur III (2112-2004 BC) are one of the most important sources for studying a significant period in the history of Mesopotamia. The kings of this dynasty ruled for a relatively long period of more than a century, marked by significant religious, political, military, and urban events that played a crucial role in the prosperity of Mesopotamia at that time. What adds to the importance of studying historical formulas is that almost every cuneiform text from any city of the dynasty is missing a historical formula that chronicles an important act by the kings of the Dynasty of Ur III.
Keywords: Ur, Formula, Achievement, Meaning, Content